Differences in Students' Thinking Skills in Making Decisions Through Online Learning Based on Google Classroom Applications on Ecosystem Materials - Nilawati Nilawati; Dewi Cahyani (Scientiae Educatia: Jurnal Pendidikan Sains)
Independent learning needs to be done in online learning to search, observe, and discover until you conclude what has been learned. Provisions in the 21st century that students must have, namely critical thinking and solving problems, it is necessary to make decisions to identify and decide the best decisions in the future, students are trained to solve a problem and must be able to make decisions. Ecosystem material with natural cases identified problems until reaching the right solution is one of the successes of decision making. The purpose of this study is to describe the online learning process based on the google classroom application for ecosystem materials and describe the differences in decision-making skills between male and female students through online learning based on the google classroom application for ecosystem materials. The method used in this research is to use a quantitative approach with a comparative research design. The research was conducted at SMAN 1 Jamblang with a sample of 14 male students and 14 female students. The quota sampling technique is a comparative quantitative method using data collection techniques and instruments in observation sheets, multiple-choice questions, and documentation: statistical descriptive analysis techniques, inference, observational analysis, and analysis of decision-making skills. The research process begins with determining the study's time and location and drawing conclusions. The online learning process for ecosystem materials is in the range of 51%-75% (good implementation), and there are significant differences in decision-making skills between male and female students through online learning based on the google classroom application on ecosystem materials for class X MIPA 1 at SMAN 1 Jamblang.